Employee engagement and improvement as important principles of TQM in public health institutes - Vrtodušić Hrgović, Ana-Marija; Črnjar, Kristina; Škarica, Ivana (2020)
Quality assurance in public health presents one of the key factors in the quality of health service. Accordingly, there is increasing awareness of the need to integrate quality systems and their principles into the healthcare system. Their role is important in the context of quality assurance in accordance with patient requirements as well as in the process of improving the quality of health care service. They are essential for the successful implementation of a quality management system and refer to customer focus, leadership, engagement of people, process approach, improvement, evidence–based decision making, and relationship management. This paper presents the results of a study among Croatian Institutes of Public Health with regard to the level of implementation of quality principles related to employee engagement, improvement and internal customer focus. Analysis focused on the relationship between focus on internal customer (employees) and improvements as well as the employee engagement and improvement respectively. Results show there is a strong positive relationship between employee engagement and improvements, while between internal customer focus and improvement the relationship has not been verified. In the context of standardization of quality of public health services, the paper aims to expand theoretical knowledge about TQM principles, with the emphasis on the employee engagement, internal customer focus (employees) and process improvement. The results can serve as a basis for improving the existing practice of quality management system implementation in the public health sector, with emphasis on employees.
Osiguranje kvalitete u javnom zdravstvu predstavlja jedan od ključnih čimbenika kvalitete zdravstvene usluge. Sukladno tome raste svijest o nužnosti integriranja sustava kvalitete i njihovih načela u zdravstveni sustav. Njihova je uloga važna u kontekstu osiguranja kvalitete u skladu sa zahtjevima pacijenata kao i u procesu poboljšanja kvalitete zdravstvene usluge. Ključni su za uspješnu provedbu sustava upravljanja kvalitetom i odnose se na : usmjerenost na kupca, vodstvo, uključenost ljudi, procesni pristup, poboljšavanje, donošenje odluka na temelju činjenica i upravljanje odnosima, U ovom se radu daje prikaz rezultata istraživanja o razini primjene načela TQM-a u Zavodima za javno zdravstvo u Republici Hrvatskoj a vezano uz uključenost zaposlenika, poboljšanja i fokus na internog kupca. Analiza je usmjerena na utvrđivanje veze između uključivanja zaposlenika i poboljšanja te fokusa na unutarnjeg kupca (zaposlenika) i poboljšanja. Rezultati pokazuju da postoji snažna povezanost između uključenosti ljudi i poboljšanja, dok između primjene poboljšanja i usmjerenosti na unutarnjeg kupca nije utvrđena povezanost. U kontekstu standardizacije kvalitete usluga u javnom zdravstvu rad ima za cilj proširiti teorijske spoznaje o TQM načelima i to posebno za uključenost zaposlenika, fokus na internog kupca (zaposlenika) i poboljšanja procesa. Dobiveni rezultati mogu poslužiti kao osnova za poboljšanje postojeće prakse implementacije TQM-a u javno zdravstvenom sustavu s posebnim naglaskom na ulogu zaposlenika u tom procesu.
Bibliografija: str. 198-200.
Summary ; Sažetak.
Keywords: Javno zdravstvo -- Zaposlenici -- Upravljanje kvalitetom -- TQM; Hrvatska